Assessments of Anthropometric, Physiological and Fitness Indicators According to Sex and Age in Participants of a Swimming Program - Rodríguez-Montero, Alejandro (2020)
This study aimed to assess anthropometric, physiological, and fitness variables related to health in 158 participants of a swimming program (89 men and 69 women), distributed in three age groups (18-29 years, 30-39 years, 40-48 years). The following protocols were used: 1) bioimpedance analysis to determine the body weight (BW), body mass index (BMI), and body fat percentage (BFP); 2) a measuring tape to measure waist circumference (WC); 3) an automatic sphygmomanometer to obtain systolic (SBP) and diastolic (DBP) blood pressure; 4) a Sit and Reach test was used to evaluate flexibility and the push-up test to evaluate muscular endurance. The results showed that BFP and (BMI) were the variables in which the highest number of people presented unhealthy values, according to international parameters. Significant differences (p<0.05) were found in SBP, DBP, WC, BFP, BMI, and muscle endurance according to sex and age. Significant correlations were found between physiological responses, physical fitness, and body composition. In conclusion, age and sex influence the results of the variables. Results were found that represent metabolic and cardiorespiratory risk factors.